2019
DOI: 10.1177/1461348418819410
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear optimal-based vibration control for systems with MR tuned vibration absorbers

Abstract: In this paper, the author proposes several approaches to nonlinear optimal-based control implementation. The vibrating system (structure) equipped with two tuned vibration absorbers (TVAs) is analysed against a system with one TVA. For control purposes, MR dampers are used instead of TVAs' passive viscous dampers. The main contribution of this research is the development and numerical verification of three nonlinear optimal-based vibration control concepts (the implementation of one-step optimal control, quasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 53 publications
(81 reference statements)
0
12
0
Order By: Relevance
“…2.0 are more than adequate for the assumed 7.69% TVA mass ratio, proving the effectiveness and validity of the control approach. 30 Neither MR damper force tracking nor oscillation frequency determination is necessary online; thus, control quality is not compromised by MR damper force constraints, while real-time control during transient, polyperiodic or random vibration phases is unimpeded; also neither offline calculation nor disturbances assumption is necessary, all essential for continual real-time control.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…2.0 are more than adequate for the assumed 7.69% TVA mass ratio, proving the effectiveness and validity of the control approach. 30 Neither MR damper force tracking nor oscillation frequency determination is necessary online; thus, control quality is not compromised by MR damper force constraints, while real-time control during transient, polyperiodic or random vibration phases is unimpeded; also neither offline calculation nor disturbances assumption is necessary, all essential for continual real-time control.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a numerical implementation of one-step nonlinear optimal control for systems with MR TVAs was realised with MATLAB/Simulink dedicated level-2 s-function and bvp4c algorithm; 30 it was also shown that iteration procedures implicating large computational loads may be omitted, utilising very short time range basis optimal problem tasks with a high-frequency resetting function and zero initial conditions for all co-state integrators. In such a case, it was demonstrated that the influence of the transversality condition (10) error was negligible for the regarded MR TVA(s) control application.…”
Section: The Implementation Techniquementioning
confidence: 99%
See 3 more Smart Citations